Förbättringsmöjligheter i en försörjningskedja under stark omvandling - Bechara, Jamil; Bhasker, Shagun (2014)
The purpose of this study is to see what improves a supply chain. We have chosen to analyze a terminal- and logistics company in Kiruna, Sweden. After we had done some further research we came up with a research problem and two research questions.  RP: What effects improvement opportunities in a supply chain? RQ1: How are current and new customers affected by logistics solutions in a supply chain considering the environmental factors? RQ2: How do the development opportunities look in a supply chain in a context of a strong transformation?The study shows that there are a couple of factors that improve a supply chain. The most important factors are price, coordination and environmental effects. Validerat; 20140818 (global_studentproject_submitter)